PERAN DIGITALISASI DALAM MENINGKATKAN INKLUSI KEUANGAN SYARIAH DI ERA EKONOMI DIGITAL - Muhammad Irfan Putra Ramadhan; Ade Ruslan Hidayat; Risna Nurul Insani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has significantly transformed the financial services sector, including Islamic finance. Digitalization is considered a strategic instrument to expand access to financial services and promote financial inclusion within the Islamic financial system. This study aims to examine the role of digitalization in enhancing Islamic financial inclusion in the era of the digital economy. Using a quantitative approach, this research employs a survey method involving [number] respondents consisting of users of Islamic financial services. Data were analyzed using descriptive statistics and regression analysis to identify the relationship between digital financial services and the level of Islamic financial inclusion. The results indicate that digitalization, particularly through mobile banking, fintech services, and digital payment platforms, has a positive and significant effect on Islamic financial inclusion. Digital financial services improve accessibility, efficiency, and user convenience, especially among unbanked and underbanked communities. Furthermore, digital-based Islamic financial services contribute to increasing public awareness and utilization of Sharia-compliant financial products. This study implies that strengthening digital infrastructure, enhancing Islamic financial literacy, and ensuring Sharia compliance in digital platforms are essential to support sustainable Islamic financial inclusion. The findings are expected to provide practical insights for policymakers, Islamic financial institutions, and stakeholders in developing inclusive and digitally driven Islamic financial ecosystems.